From analysis to coaching - the need for objective feedback - Hughes, M. (coachesinfo.com)
The coaching process is about enhancing performance by providing feedback about the performance to the athlete or team. Researchers have shown that human observation and memory, wonderful though they are, are not reliable enough to provide accurate and objective information for high-performance athletes. Objective measuring tools are necessary to enable the feedback process. These can take the form of video analysis systems post-event, both biomechanical or computerised notation systems, or the use of in-event systems. Hand and computerised notation systems provide the same sort of data, both intrinsically being the same process, and they are used for the same purposes: analysis of movement, tactical evaluation, technical evaluation and statistical compilation. The recent developments in both computer and video technologies have transformed the approach of performance analysts and, consequently, their use in the coaching process. To ensure that accurate and reliable data are gathered for analysis for the coach, considerable training of the operatives is necessary, making the application of any of these systems more and more a specialism. Because of the developing nature of the disciplines involved, not enough fundamental questions have been asked about the processes we apply, but we are hoping that some of these will be addressed in this article.